STANDARDIZATION OF GERMINATION TEST AND RESPONSE TO NACL SALT STRESS IN Toona cliliata SEEDS - de Medeiros, Letícia Ramon; Monteiro, Manoela Andrade; Migliorini, Patrícia; Lazarotto, Marilia; de Tunes, Lilian (Floresta, 2015)
Abstract The objective of this study was to evaluate the germination of Australian cedar seeds (Toona ciliata M. Roem) in three different substrates and two photoperiods and evaluate the effect of salt stress with sodium chloride (NaCl) on the viability and vigor of seeds, conducting two experiments. The first experiment was conducted in a constant temperature room at 25 C and two light regimes 12h 24h white light; and three substrates: sand, between paper and on paper. Evaluations were performed on the seventhand twenty-first day after sowing. Results were expressed as percentage of Normal Seedlings, Abnormal Seedlings and Dead Seeds, Number of True Leaves, Fresh, Dry Matter, Seedling Length and Root. The second experiment used constant 25 C and photoperiod of 12 hours light. With treatments T1 (0mM: distilled water); 25mMNaCl T2; T3 50mMNaCl; T4 and T5 100mMNaCl 75mMNaCl. We evaluated PCG, G, IVG, CP, CR. The photoperiod of 24h light, does not influence the final seed germination and the use of paper on substrate provided the highest percentage of germinated seeds. As to the effect of salt stress, the concentration of 50mMsalt, caused damage to the development of seedlings. Resumo Padronização do teste de germinação e resposta ao estresse salino por NaCl em sementes de Toona ciliata. O objetivo do trabalho foi avaliar a germinação de sementes de cedro australiano (Toona ciliata M. Roem) em três substratos com dois fotoperíodos e avaliar o efeito do estresse salino com cloreto de sódio (NaCl) na viabilidade e vigor de sementes. O experimento I foi conduzido em ambiente com temperatura constante a 25 ºC e dois regimes de luminosidade, 12h de 24h de luz branca; três substratos: areia, entre papel e sobre papel. As avaliações foram realizadas no sétimo e vigésimo primeiro dia após a semeadura. Os resultados expressos em porcentagem de Plântulas Normais, Plântulas Anormais e Sementes Mortas, número de Folhas Verdadeiras, Massa Fresca, Massa Seca, Comprimento de Plântula e Raiz. O experimento II utilizou temperatura constante a 25 ºC e fotoperíodo de 12 horas luz. Com os tratamentos T1 (0 mM: água destilada); T2 25 mMNaCl; T3 50 mMNaCl; T4 75 mMNaCl e T5 100 mMNaCl. Avaliando-se PCG, G, IVG, CP e CR. O fotoperíodo de 24h de luz, não influencia na germinação e o uso do substrato sobre papel proporcionou a maior germinação. Quanto ao efeito do estresse salino, a concentração de 20 mM de sal, prejudicou o desenvolvimento das plântulas. Palavras-chave: Sementes florestais; análise de sementes, vigor, salinidade.